What Impedes General Practitioners' Identification of Mental Disorders at Outpatient Departments? A Qualitative Study in Shanghai, China - Hanzhi Zhang; Dehua Yu; Zhaoxin Wang; Jianwei Shi; Jie Qian (Ubiquity Press, 2019)
Background: Mental disorders endanger people's health and lives. General practitioners (GPs) play a valuable role in identifying and treating mental disorders in outpatient clinical settings. However, there are obstacles for GPs' identification in developing countries. Objective: This study's aim was to identify the related obstacles and to propose optimized strategies. Methods: We conducted qualitative interviews with 26 GPs from seven randomly sampled community healthcare centers in Shanghai, China. The interview guide was based primarily on the items from mental status evaluation. After transcribing, coding, condensing, and categorizing talking content, we summarized the theme structure and results. Findings: GPs lacked the confidence and skills to conduct psychiatric evaluation and seldom conducted it. Patients' behaviors also influenced whether evaluations were conducted. The GPs expressed that they were short of strategies and wished to be well trained and have sufficient practice. We found that two major reasons impeded GPs' identification. First, the GPs had difficulty making a diagnosis: they lacked diagnostic ability and confidence, they had misunderstandings about diagnoses, and they had unclear qualifications for making psychiatric diagnoses. Second, the GPs lacked skills for evaluation and reevaluation: their evaluation had inadequacies of contents and subjects; they lacked mental state examination evaluation, communication, and severity assessment skills and knowledge. Conclusions: This study found that it is difficult for GPs in developing countries to become competent in the diagnosis and systematic evaluation of mental disorders without external help. Unclear qualification also limited GPs' diagnoses of mental disorders. We proposed that optimized strategies to overcome these challenges lie in support of changes in policy, programs, and utilizing effective tools, such as the mhGAP, GMHAT/PC, BVC, Grille's assessment tool, and telemedicine.